2009
DOI: 10.1111/j.1365-2230.2008.03006.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic administration of chloroquine in discoid lupus erythematosus reduces skin lesions via inhibition of angiogenesis

Abstract: Background. Discoid lupus erythematosus (DLE) is a chronic cutaneous form of lupus erythematosus, characterized by inflammation and scarring skin lesions, with lymphocyte infiltration and vasodilation. Antimalarial drugs have beneficial therapeutic effects in DLE, partially resulting from their immunomodulating and photoprotective properties. The possible influence of these drugs on angiogenesis has not been previously evaluated. Aims. To investigate the impact of chloroquine (CQ) treatment on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…However, its role in HIV infection remains controversial. In the present study, CQ was administrated at a single oral dose of 250 mg once daily for 24 weeks, a similar dosage to that used in autoimmune diseases [13][14][15]. In our study population, CQ was well tolerated and no grade 3 or 4 side effects were observed during the study.…”
Section: Discussionmentioning
confidence: 92%
“…However, its role in HIV infection remains controversial. In the present study, CQ was administrated at a single oral dose of 250 mg once daily for 24 weeks, a similar dosage to that used in autoimmune diseases [13][14][15]. In our study population, CQ was well tolerated and no grade 3 or 4 side effects were observed during the study.…”
Section: Discussionmentioning
confidence: 92%
“…VEGF is a multifunctional peptide that is capable of inducing endothelial cell proliferation and angiogenesis both in vivo and in vitro. VEGF induces microvascular hyperpermeability, and its angiogenic effect plays a role in a variety of physiological and pathological conditions-including wound healing, blister formation, and skin neoplasia [15][16][17][18]. The raised plasma levels of VEGF have been noted not only in vascular tumors of the skin (such as Kaposi's sarcoma) but also in chronic inflammatory and autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine and HCQ possess activity that inhibits angiogenesis, and there is a report of a decrease in vessels in the dermis. 9 HCQ was effective against erythema and telangiectasia, but that may have reflected the fact that there was very little change in the atrophy or scarring. The considerable improvement in the telangiectasia in case 3 may have been attributable to the activity of HCQ that inhibits angiogenesis.…”
Section: Discussionmentioning
confidence: 99%